2010
DOI: 10.1177/1470320310374215
|View full text |Cite
|
Sign up to set email alerts
|

Persistent microalbuminuria after treatment with renin-angiotensin axis blockers: causes and results of treatment intensification

Abstract: Persistent microalbuminuria was associated with poor blood pressure control and inadequate drug dosage. Low frequency of administration of drugs at night and inappropriate once-daily pills intake were frequent. Strict control of blood pressure and intensive RAA blockade significantly reduced the prevalence of microalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Indeed, ACE inhibitors or ARBs are often the first drugs used for renal protection in chronic kidney disease, but even when these RA system-inhibiting drugs are used, there may be no reduction in albuminuria, or albuminuria may develop during the course of treatment. [26][27][28] It is well known that the renal protective effect of RA system inhibitors is not sustained over the course of chronic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ACE inhibitors or ARBs are often the first drugs used for renal protection in chronic kidney disease, but even when these RA system-inhibiting drugs are used, there may be no reduction in albuminuria, or albuminuria may develop during the course of treatment. [26][27][28] It is well known that the renal protective effect of RA system inhibitors is not sustained over the course of chronic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for diagnosis have been published elsewhere [16]. An initial measurement of albumin excretion ratio by stick (MICROALBUSTIX©, Bayer AG, Leverkusen, Germany) was performed and, when it rendered positive, the measurements of UAE was reassured in 24-h urine collections.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous report we have described the possible causes of resistant microalbuminuria and the results of intensive treatment [16]. This report describes the characteristics of patients who became normoalbuminuric compared to those who remained microalbuminuric after modifying treatment.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7] However, even with the administration of RAS inhibitors, failure to achieve adequate anti-albuminuric effects, renoprotective effects and a reduction in cardiovascular events has also been reported. [8][9][10][11][12] To achieve more complete RAS inhibition in patients with type 2 diabetes, concomitant treatment with different types of RAS inhibitors has been promising. However, some clinical studies, including those in Japanese patients, have shown that concomitant treatment with an ACEI and ARB, or also including a direct renin inhibitor, may not provide a clinical synergistic effect in reducing cardiovascular events or preventing a decline in renal function, but conversely, may cause an increase in the incidence of adverse reactions such as hyperkalemia and acute renal insufficiency.…”
Section: Introductionmentioning
confidence: 99%